The Yugoslavian System, A Communal System? - Bastos, Eduardo (Universidad del Pacífico, 1978)
It is feeling with more urgency the need to revitalize the political structures of nations, trying to embody the social body from which they come. In socialist countries the proletariat laborers, conscious of their strength, make feel from time to time their disturbing presence at the party's bureaucratic apparatus which officially represents them. This is, without doubt, the profound meaning of "revolution of December" 70 in Poland, not to mention the spring of 68 in Czechoslovakia. "It is, indeed, the Polish case, the first time - André Martin wrote - for fifty years in the working class of a country under communist rule who took to the streets, wins, sow the panic in the heights of the ruling apparatus and requires a dictator to disappear in the full sense of the word. However, officially the political regime in Poland represents the popular working class. "